أسس بناء الدولة في القرآن الكريم والسنة النبوية : تركيا نموذجا - شوشة، حسام موسى محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The purpose of this research is to examine the foundations of state-building in the Holy Quran and the Sunnah of the Prophet Muhammad and using the State of Turkey under the rule of the Justice and Development Party (AK Parti) as an applicable case study of state-building. This research clarified the concept of state is “a group of people living in a geographical location and ruled under the Islamic Law”. The research also shed light on types of states presented in the Quran and Prophetic Tradition, their characteristics, and the end outcome of each of them. Furthermore, the research examined what constitutes the existence of the state, namely: the nation or the people, the territory or the land and the authority. The research also clarified the necessity of the existence of the state in the light of the Holy Quran and Sunnah. The research concluded that the state is a “firm establishment founded on strong foundations, resistant to the demolition factors, keeps up with the rapid scientific and technological progress, and guided by the book Allah and the Prophetic Tradition”. The research listed the scope of foundations of the state-building which are: faith and morality, military and security, social and psychological, educational and scientific, economic and financial, and finally legislative and legal. The final chapter is a case study of the Turkish state under the rule of the. The thesis discussed the emergence of the modern Turkish state, and the factors that led to the emergence of Justice and Development Party (AK Parti), of Islamic orientation, and the most prominent Islamic activists' figures in Turkey. In addition, the research analysed the grounds on which the Party established the state (Turkey); to examine this development, the research analysed the party's administrative role in relation to the critical international issues as well as the laws that were passed under the rule of Justice and Development Party, and to which extent they fulfilled Maqasid al-Shari'a (Purposes of Islamic Law). The researcher used the inductive method and the analytical approach. The research concluded a number of results; the most important of which are: 1.The concept of the state in the Islamic heritage and thought is completely different than western concept of the state. 2. The just state is destined for permanence and continuity, even if it a non-Muslim state, and the unjust state is destined to destruction and perishment even if it is a Muslim state. 3. The existence of the state is a religious duty and a human necessity. 4. The foundations mentioned in the research must be available in order to successfully complete the state-building process. 5. Clear legislation and a firm constitution that does not change according to whims of people can enable the stability and continuity of the state. 6. The success of the Justice and Development Party in managing the affairs of the state is the result of the grace of Allah, and then the sincerity of the individuals managing the country, and their ability in taking the means that lead to success, and continually working in the best interest of people and the country and a whole.